PERAN ORANG TUA DALAM PEMBENTUKAN KEPRIBADIAN SOSIAL ANAK: STUDI KASUS DI DESA SITIREJO KECAMATAN TAMBAKROMO KABUPATEN PATI - Putri Mulyani; Imaniar Purbasari; Santoso (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes a study about the role of parents in the formation of a child's social personality. The formulation of the problem was how the role of parents could affect the children’s social personality building and the factors of children's social personality building at Sitirejo Tambakromo, Pati. The study used the descriptive-qualitative method as the stage in conducting the research. The study used data collection techniques that included the stages of observation, in-depth interviews, documentation, and taking notes. The data analysis used was descriptive qualitative data analysis. The result showed that the role of parents provided an influence on the diversity of children's personalities in Sitirejo Tambakromo. The personality diversity that children have was influenced by the parents’ role. Although the parents were similar to play the roles, the attitudes in carrying out their roles were different. It provided the different influences on children’s personalities. The factors in the form of the children's personality indicated that the children's personality was influenced by two factors, internal and external factors. According to the researcher's analysis, there are two out of ten children whose personality was influenced by internal factors and eight of ten children whose personality was influenced by external factors